HUBUNGAN ANTARA KREATIVITAS GURU DAN MOTIVASI BELAJAR SISWA KELAS TINGGI MI AR-RAHMAN PAJEKKO KECEMATAN BAREBBO KABUPATEN BONE - Sudarto Sudarto; Asriadi Asriadi; Susanti Susanti (JISOS: JURNAL ILMU SOSIAL, 2022)
This study is a quantitative study with a correlation design that aims to determine whether or not there is a relationship between teacher creativity and student motivation for high grade students at MI Ar-Rahman Pajekko. The population in the study were all high school students of MI Ar-Rahman Pajekko which were also used as samples with a total of 45 students. The sample was selected using a non- probability sampling technique, namely saturated sampling. Data collection is done by using a questionnaire. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of teacher creativity research have an average of 22,91 and a percentage of 79,00% with a good category and the learning motivation of high-class students has an average of 23.41 and a percentage of 80.68% with a very good category. Based on the results of inferential statistical analysis, the tcount value (2,38878) is greater (>) the ttable value (1,68107) at the 5% significance level. Thus ????0 is rejected and ????1 is accepted. The results obtained in this study are that there is a significant relationship between teacher creativity and high grade students' learning motivation at MI Ar-Rahman Pajekko, Barebbo District, Bone Regency